Grammar and Composition - Willis, Hulon (New York : Holt, 1976)
These instructional objectives have been selected from materials submitted to the Curriculum Laboratory of the Graduate School of Education at UCLA by Donald M. Desfor. Arranged by major course goals, these objectives are offered simply as samples that may be used where they correspond to the skills, abilities, and attitudes instructors want their students to acquire. These objectives may also serve as models for assisting instructors to translate other instructional units into specific measurable terms. For other objectives in related courses see: ED 033 392 (Remedial English); ED 033 393 (English [Subject A]); ED 033 394 (English Composition); and JC 710 125 (English Composition). (MB)
Microfiche.
Keywords: Behavioral Objectives; English; English Instruction; Grammar; Two Year Colleges; Writing (Composition)